2019
DOI: 10.1088/1757-899x/677/2/022014
|View full text |Cite
|
Sign up to set email alerts
|

Research on Tissue Culture Rapid Propagation Technology of Taiwan Lily

Abstract: This experiment selected Taiwan lily as experimental material to study the different ages of lily to produce different explants to induce differentiation, through subculture and the optimal conditions for tissue culture outdoor refining, and then the experimental staff established Systematic Taiwan lily flower tissue culture and rapid propagation technology. Studies have shown that the optimal medium for differentiation of Taiwan lily flower scales (winter sampling) is MS+0.2 ug/L GA3+0.1 mg/L NAA+1 mg/L 6-BA;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The process of in vitro propagation, not only allows for the rapid proliferation of plants, but it is also possible to produce virus-free plant material from the meristem or uninfected tissues (Huong, Gioi, & Van Thang, 2017). It has been reported that a significant number of primary lilies and commercial lilies have been successfully propagated in vitro (Li, Xia, Liang, & Yang, 2019). Through the process of in vitro propagation, not only is there a continual supply of bulblets, but it is also possible to obtain plants that are perfectly true to type and free of disease (Gochhayat, Beura, & Subudhi, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The process of in vitro propagation, not only allows for the rapid proliferation of plants, but it is also possible to produce virus-free plant material from the meristem or uninfected tissues (Huong, Gioi, & Van Thang, 2017). It has been reported that a significant number of primary lilies and commercial lilies have been successfully propagated in vitro (Li, Xia, Liang, & Yang, 2019). Through the process of in vitro propagation, not only is there a continual supply of bulblets, but it is also possible to obtain plants that are perfectly true to type and free of disease (Gochhayat, Beura, & Subudhi, 2017).…”
Section: Introductionmentioning
confidence: 99%